Technique for Failed Total Wrist Arthroplasty Conversion to a Total Wrist Arthrodesis with Allograft Interposition - D'Amore, Taylor; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2020)
The frequency of prosthetic total wrist arthroplasty continues to increase. With this increase comes the expected subsequent increase in need for revision or salvage procedures. The technique presented here involves the use of a cortical allograft interposition graft to restore bone stock and length for failed total wrist arthroplasty.
Keywords: total wrist arthroplasty; wrist arthrodesis; revision arthroplasty